The association between attention deficit/hyperactivity disorder and internet addiction: a systematic review and meta-analysis - Wang, Bing-qian; Yao, Nan-qi; Zhou, Xiang; Liu, Jian; Lv, Zheng-tao (BMC psychiatry, 2017)
This study aimed to analyze the association between Attention Deficit/Hyperactivity Disorder (ADHD) and Internet addiction (IA). A systematic literature search was performed in four online databases in total including CENTRAL, EMBASE, PubMed and PsychINFO. Observational studies (case-control, cross-sectional and cohort studies) measuring the correlation between IA and ADHD were screened for eligibility. Two independent reviewers screened each article according to the predetermined inclusion criteria. A total of 15 studies (2 cohort studies and 13 cross-sectional studies) met our inclusion criteria and were included in the quantitative synthesis. Meta-analysis was conducted using RevMan 5.3 software. A moderate association between IA and ADHD was found. Individuals with IA were associated with more severe symptoms of ADHD, including the combined total symptom score, inattention score and hyperactivity/impulsivity score. Males were associated with IA, whereas there was no significant correlation between age and IA. IA was positively associated with ADHD among adolescents and young adults. Clinicians and parents should pay more attention to the symptoms of ADHD in individuals with IA, and the monitoring of Internet use of patients suffering from ADHD is also necessary. Longitudinal studies controlling for baseline mental health are needed.